Pre-operative risk factors assessment to anticipate technical difficulty in laparoscopic cholecystectomy for acute cholecystitis (BIRDEM Medical Journal, 2025)
Background: Laparoscopic cholecystectomy (LC) has rapidly become the operation of choice for routine gallbladder (GB) removal. LC can be difficult in certain patients. This study aimed at finding out the pre[1] operative risk factors to anticipate technical difficulty in laparoscopic c holecystectomy in acute cholecystitis. Methods: This cross sectional observational (analytical )study was performed in the department of Surgery, BIRDEM General Hospital, Dhaka for a period of 18 Months. Before starting this study ethical clearance was obtained from Institutional Review Board (IRB) of Bangladesh Institute of Research and Rehabilitation in Diabetes (BIRDEM) general Hospital. A total of 70 patients with acute cholecystitis undergoing laparoscopic cholecystectomy were enrolled in this study as per inclusion criteria. A written informed consent was taken from all the participants after explaining the objective and their role to the study. After the enrolment, detailed history and physical examination was done. A structured questionnaire was used for each of the participants to collect data. In all cases, patients underwent complete blood count (CBC), C-reactive protein (CRP), Liver function tests and abdominal ultrasonography to evaluate anatomical variations in the biliary tract , in some selected cases magnetic resonance cholangiopancreatography (MRCP) or endoscopic retrograde cholangio-pancreatography (ERCP) was also conducted before surgery when choledocholithiasis was suspected. Per-operative difficulty was anticipated based on longer operative time, amount of blood loss, pericholecystic odema and intraabdominal adhesion. Data regarding absence or presence of factors were collected and difficulty in laparoscopic cholecystectomy was noted. All the collected data was entered and analyzed on Statistical Packages for Social Sciences (SPSS version-26). Result: The study included 70 participants with a mean age of 49.6 years, predominantly male (62.9%). Technical difficulty during laparoscopic cholecystectomy (LC) was observed in 64.3% of cases. Significant factors associated with technical difficulty included chronic liver disease (OR 1.6, p=0.022), previous surgery (OR 1.16, p=0.011), jaundice (OR 1.5, p=0.028), and a positive Murphy’s sign (OR 1.7, p=0.018). Elevated WBC count (22.5 ± 15.9 x10^9/L) (p=0.008), CRP (112.7 ± 50.2 mg/L, p=0.001), ALP (181.7 ± 98.1 U/L) (p=0.001), increased gallbladder wall thickness (3.35±1.7 mm, p=0.019), pericholecystic edema (p=0.027), and intra-abdominal adhesions (p=0.010) were significantly correlated with increased surgical difficulty. The presence of a normal gallbladder was associated with a reduced likelihood of technical challenges (OR 5.0, p=0.001). Conclusion: The identification of preoperative predictors allows anticipation of technical challenges with managing potential complication in laparoscopic cholecystectomy (LC) and enhances surgical safety in acute cholecystitis. BIRDEM Med J 2025; 15(3): 111-119